E-Government and Transparency in Georgia: An Analysis of County Websites as Citizen Portals to Democracy - Yaccarino, Elizabeth Kay (My University, 2025)
The Founding Fathers of the United States, concerned with protecting individual rights and responsibilities, provided checks and balances to ensure wise governance. As the nation matured, laws reinforcing the rights of citizens were passed to mandate that government functions be conducted in an open manner. As technology evolved, the legislative mandates did as well and today, the internet is considered an integral part of government, both utilitarian in its functions but also with respect to openness and transparency. The internet is also an integral part of direct government-to-citizen contact and interaction. Given that counties function as government entities, imbued with powers mandated by the state that exceed those granted to cities, and serving as the closest level of governance to all citizens in Georgia, 36 county websites are studied: three in each of the 12 Regional Commission districts, based on population size: small, median, and large. Each website is studied and graded according to a unique checklist developed specifically for this purpose, utilizing established guidelines for open governance and transparency. The results vary between the counties and regions, with factors such as size, location, education and affluence potentially affecting the outcomes. As no other transparency project of this scale has yet been conducted at the county-level in Georgia, this dissertation will fill gaps in knowledge for local, state and national governments and organizations seeking this knowledge.
Keywords: Dissertations, Academic--United States; Electronic records; Georgia; Local government; County government; Public administration; Transparency (Ethics) in government; Websites